2013-06-09 - Ai, Xiao-Wei, (Utilitas Mathematica, 2013)
Wiener index is defined as the sum of distances between all pairs of vertices in a nontrivial connected graph. In this paper,we use Wiener index to give a new sufficient condition for a connected bipartite graph to be Hamiltonian.